Concepciones sobre los sistemas de adquisición de datos en el trabajo de laboratorio en Física - Cardona-Zapata, Mónica Eliana; Pabón Rúa, Daniel; López Ríos, Sonia Yaneth (Revista Científica, 2021)
It has been reported in the literature that in the practical laboratory work in physics there is a clear split between theory and practice that accounts for a distorted view of the construction of scientific knowledge. In addition, this vision has made the development of higher-order cognitive processes of the subjects to be disadvantaged by limiting this learning space to following guidelines conducted with pre-established objectives. In this sense, a theoretical-methodological proposal was built based on Gerard Vergnaud’s Theory of Conceptual Fields, in which practical laboratory work and the use of technologies such as data acquisition systems (DAS) are articulated to address situations that favor conceptualization; therefore, favoring the representation processes that acquire great importance when considering the abstract nature of physics. The proposal was implemented with a group of future teachers in the area of natural sciences from a Bachelor's program at an official university, with whom a case study was carried out from a qualitative perspective. From the results, it can be affirmed that SAD allow relationships between variables to be established, reduce uncertainty in data collection, and play an important role in the process of representing physical phenomena.